Assessment of the incidence and preventability of adverse events in hospitals: an integrative review - Ariane Cristina Barboza Zanetti; Carmen Silvia Gabriel; Bruna Moreno Dias; Andrea Bernardes; André Almeida de Moura; Andréia Boldrini Gabriel; Antônio José de Lima Júnior (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To highlight the scientific production related to the use of the retrospective chart review methods to assess the incidence and preventability of adverse events in hospitals. Method: An integrative review in the MEDLINE, LILACS, SCOPUS, Web of Science and EMBASE databases conducted in May 2019 with the following guiding question: What is known about the retrospective chart review methods to assess the incidence and preventability of adverse events in hospitals? Subsequently, the categorization, synthesis, and classification of the evidence levels of the included publications were performed. Results: In the 13 selected studies, the instruments adopted to assess the occurrence of adverse events were the Harvard Medical Practice Study, the Canadian Adverse Event Study, the Quality in Australian Health Care Study, and the Global Trigger Tool. Incidence ranged from 5.7 to 14.2%, while preventability ranged from 31 to 83%. Conclusion: Differences in incidence and preventability were found, showing different results in the quality of care provided, the information registered in medical records, the screening criteria used, and the assessments of the reviewers.